For a Typology of Participation in Community Artistic Practices: the experience of three theater groups in Brazil and Portugal - Cruz, Hugo; Bezelga, Isabel; Menezes, Isabel (Revista Brasileira de Estudos da Presença, 2022)
The article aims to address the participatory dimension as a central feature in contemporary artistic creation, deepening the relationship between processes and results. It has as a starting point the practices of three theater groups in Brazil and Portugal, articulating them with the literature on community artistic practices and civic and political participation. From empirical data, based on participant and non-participant observation and gathering of field notes, structural dimensions of the qualities of the participation experiences in artistic processes were identified, namely: forms of participation of communities (non-professional); dynamics of creative processes; core themes; relationship between professionals and communities; and spaces of creation and presentation.